(untitled) - Gleick, Peter H. (Washington, 2006)
he individual essays on concrete aspects of freshwater in the world today refer to matters that are critical and current. The tables and statistics at the end of the book are up to date references that are extremely useful to gauge the state of freshwater use and abuse in all regions of the world, an unvaluable resource for local activism anywhere in our planet.
Keywords: Water supply,Freshwater,Cung cấp nước